Detection of Unhealthy Region of Plant Leaves Using Texture Features - Malini, S; Jeyalakshmi, T. Ratha (International Journal of Computer Sciences and Engineering, 2025)
Crop cultivation plays a necessary function in the agricultural field. Presently, the loss of food is mainly due to infected crops, which reduce the manufacture rate. Plant diseases have curved into a problem as it can cause chief reduction in both quality and quantity of agricultural products. Automatic detection of plant diseases is a critical research topic as it may prove benefits in monitoring large fields of crops, and thus automatically discover the symptoms of diseases as soon as they appear on plant leaves. The proposed approach consists of four main steps, first the input image is converted using color transformation into RGB image and then as a second step the green pixels are masked and removed by segmentation process using specific threshold value, the texture features are extracted then passed through the classifier